A Comparative Study of Patients' Attitudes Toward Clinical Research in the United States and Urban and Rural China. Issue 2 (15th January 2015) - Wu, Elizabeth; Wang, Tianyi; Lin, Tammy; Chen, Xisui; Guan, Zhe; Cao, Claudia; Rao, Huiying; Yang, Ming; Feng, Bo; Pui, Sandra; Chan, Melvin; Fu, Sherry; et al.
Abstract: As the number of clinical trials conducted in China increases, understanding Chinese attitudes toward clinical research is critical for designing effective and ethical studies. Two survey studies were conducted in 2012 and 2013 to compare patient attitudes toward clinical research and factors affecting research participation in the United States and urban and rural China. We surveyed 525 patients in 2012 (186 US, 186 urban, 153 rural China) and 690 patients in 2013 (412 US, 206 urban, 72 rural China). US patients were more likely to have no concerns regarding research participation than Chinese patients. Most common concerns of US patients were safety, privacy and confidentiality, and time required. Safety was a top concern for many Chinese. Chinese patients, particularly rural Chinese, were more concerned about the likelihood of self‐benefit, and receiving free medical care and financial incentive had greater influence on their participation. Being informed of the freedom to choose whether to participate or to leave a study was less important to Chinese patients. Our study provides important insights into Chinese patients' attitudes toward clinical research and the need to educate them about their rights. These findings help in designing cross‐cultural clinical studies that maximize enrollment while upholding Western ethical standards.